Anaerobic leaching of covellite by Thiobacillus ferrooxidans - Donati, Edgardo Ruben (1997)
Thiobacillus ferrooxidans was able to grow under anaerobic conditions on copper sulphide with ferric ion as the electron acceptor. The dissolution of covellite under these conditions (68% after 35 days) was higher than values observed aerobically in cultures with similar media composition and almost as high as under aerobic conditions without iron. From these results we propose a mechanism for anaerobic bioleaching of covellite in the presence of ferric iron and speculate that it may occur in leach dumps where the oxygen concentration is, as reported elsewhere, very low.